Outcomes following Placement and Removal of Transvaginal Cerclage in at Risk Pregnancies: A Single Center Experience - Henry Adekola; Jennifer Addo; Elizabeth Ramsey Unal; Emma James; Vivek Prakash; Robert Abrams (Journal of Pregnancy)
Objective. The objective of this study was to estimate the time between removal of cerclage and delivery, stratified by indication for cerclage placement (elective or non-elective). Additionally, delivery within 72 hours after cerclage removal was compared between elective and non-elective cerclage placement, as well as between ultrasound-indicated and physical examination-indicated cerclage placement. Design. A single-center retrospective cohort study. Participants/Materials, Setting, and Methods. Clinical information of 72 pregnant women who underwent transvaginal cerclage over a 4-year period was obtained. Comparisons were made between elective (history-indicated) and non-elective (ultrasound or physical examination-indicated) cerclage placement. Comparisons were also made between physical examination-indicated and ultrasound-indicated cerclage. Results. Compared to those who had a non-elective cerclage, women undergoing elective cerclage were more likely to have history of cervical treatment (44% vs. 15%, p=0.02), and spontaneous preterm delivery (92% vs. 61%, p=0.003). There was no difference in the rate of delivery ≤72 hours following cerclage removal between women who had elective cerclage and those who had non-elective cerclage (46% vs. 58%, p=0.47). Women who had an elective cerclage were more likely to have elective cerclage removal ≥36 weeks (71.8% vs. 39.4%, p=0.01), compared to those who had undergone non-elective cerclage. The rate of delivery ≤72 hours following removal of cerclage was greater in women who had a physical examination-indicated cerclage compared to women who had ultrasound-indicated cerclage (80% vs. 39%, p=0.04). Among women who had an elective cerclage, there was no difference in the rate of delivery at ≤72 hours between those who had elective cerclage removal at 36 weeks compared to those electively removed at 37 weeks (31% vs. 58%, p=0.30). No complications such as fetal demise, iatrogenic amniotic membrane rupture, hemorrhage, or cervical laceration were reported within this cohort. Conclusion. Cerclage indication should be considered prior to scheduling elective cerclage removal. Women who had an elective cerclage are most likely to get it electively removed at 36 weeks compared to their counterparts who had a non-elective cerclage. Furthermore, women who had a physical examination-indicated cerclage are most likely to deliver within 72 hours of cerclage removal.